Preoperative pelvic floor muscle exercise for continence after radical prostatectomy: a systematic review and meta-analysis - Zhou, Luqiang; Chen, Yu; Yuan, Xiaojuan; Zeng, Lijing; Zhu, Jingzhen; Zheng, Ji (Frontiers in Public Health, 2023)
Objective We performed a systematic review and meta-analysis to evaluate the effect of preoperative pelvic floor muscle exercise on urinary incontinence after radical prostatectomy. Methods We searched the literature for randomized controlled trials evaluating the diagnostic analysis of preoperative pelvic floor muscle exercise (PFME) and postprostatectomy incontinence in the MEDLINE, EMBASE, PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO, China Biomedical Literature Database, China Journal Full-text Database, Wanfang Database and Weipu Database. The retrieval time limit is from the establishment of the database to January 2023. We used a risk ratio with accompanying 95% confidence interval (CI) to express estimates. Reviewer Manager (RevMan) 5.1.0 was used to complete all statistical analyses. Results Twelve studies were included based on the selection criteria. The total number of patients included in the final analysis was 1,365. At 1th month, there was no difference in continence rates between the groups [odds ratio (OR): 0.47; 95% confidence interval (CI), 0.22–1.02, p = 0.06]. At 3th month, there was statistically significant difference in PFME group before operation (OR: 0.61; 95% CI, 0.37–0.98, p = 0.04). At 6th and 12th months, there was no difference between groups (OR: 0.57; 95% CI, 0.28–1.17, p = 0.13), (OR: 0.56; 95% CI, 0.27–1.15, p = 0.12). Conclusion Preoperative pelvic floor muscle exercise can improve postoperative urinary incontinence at 3rd months after radical prostatectomy, but it cannot improve urinary incontinence at 6th months or longer after surgery, which indicates that preoperative PFME can improve early continence rate, but cannot improve long-term urinary incontinence continence rate.